A hypothesis for pathobiology and treatment of COVID‐19: The centrality of ACE1/ACE2 imbalance. (22nd May 2020) - Sriram, Krishna; Insel, Paul A.
Abstract : Angiotensin Converting Enzyme2 is the cell surface binding site for the coronavirus SARS‐CoV‐2, which causes COVID‐19. We propose that an imbalance in the action of ACE1‐ and ACE2‐derived peptides, thereby enhancing angiotensin II (Ang II) signalling is primary driver of COVID‐19 pathobiology. ACE1/ACE2 imbalance occurs due to the binding of SARS‐CoV‐2 to ACE2, reducing ACE2‐mediated conversion of Ang II to Ang peptides that counteract pathophysiological effects of ACE1‐generated ANG II. This hypothesis suggests several approaches to treat COVID‐19 by restoring ACE1/ACE2 balance: (a) AT receptor antagonists; (b) ACE1 inhibitors (ACEIs); (iii) agonists of receptors activated by ACE2‐derived peptides (e.g. Ang (1–7), which activates MAS1); (d) recombinant human ACE2 or ACE2 peptides as decoys for the virus. Reducing ACE1/ACE2 imbalance is predicted to blunt COVID‐19‐associated morbidity and mortality, especially in vulnerable patients. Importantly, approved AT antagonists and ACEIs can be rapidly repurposed to test their efficacy in treating COVID‐19. LINKED ARTICLES: This article is part of a themed issue on The Pharmacology of COVID‐19. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.21/issuetoc Abstract :